Instant Messaging Forensic Analysis on Android Operating System - Guntur Maulana Zamroni; Imam Riadi (Universitas Muhammadiyah Malang, 2019)
WhatsApp (WA) is one of the Instant Messaging (IM) applications used by many people. WA and mobile devices cannot be separated from the possibility of misuse such as for criminal purposes. To handle a crime case involving a mobile device, the investigator needs to use suitable forensic tools and mobile forensic methodology so that the results can be approved and accepted by the law. This research conducted a forensic analysis of WA on unrooted Samsung C9 Pro devices using Belkasoft Evidence, Oxygen Forensic, Magnet AXIOM, and WA Key/DB Extractor. This research gives suggestion about forensic tools for conducting forensic analysis related to WA. From the research can be seen that there is no tool that can be used to obtain all the WA artifact parameters used in the research. The combination of the Magnet AXIOM and WA Key/DB Extractor is known to get the best results and meets the WA artifact parameters.